Ballistics - Osheku, Charles (IntechOpen, 2019)
The edited volume Ballistics is a collection of reviewed and relevant research chapters, offering a comprehensive overview of recent developments in the field of engineered mechanics. The book comprises single chapters authored by various researchers and edited by an expert from the respective research area. Each chapter is complete in itself but united under a common research study topic. This publication aims to provide a thorough overview of the latest research efforts by international authors on engineered mechanics and opens new possible research paths for further novel developments.